Syncretizing Culture and Faith: The Kurang Labih Principle in Kalimantan - Yuli Apriati; Zainudin Bin Hassan; Rahmat Nur; Muhammad Rezky Noor Handy; Cucu Widaty (Universitas Islam Negeri Madura, 2025)
This article aims to identify and analyze the value of the local wisdom “Kurang Labih” in the traditional river-based trading system, specifically as a form of local wisdom among the Banjar people. Values ​​rooted in the local wisdom of the Banjar people, such as the value of “Kurang Labih,” remain the primary foundation in the governance of their social life, especially in traditional trade practices. This research employs a qualitative approach, utilizing a case study method. Data were collected through observation, interviews, and documentation to produce a comprehensive writing on cultural phenomena. The study's results found that the culture and local wisdom in traditional trade at this floating market possess the value of “Kurang Labih,” which can make the trade process mabrur, or moral, namely a trade that prioritizes goodness, virtue, and blessings received from Allah SWT. The local wisdom of “Kurang Labih” at the Lok Baintan floating market is strongly influenced by Islamic values, considering that all traders are Muslim, and this value is passed down from generation to generation. The value “Kurang Labih” reflects the principle of caution in buying and selling, a moderate attitude, and the pursuit of blessings, thus creating acceptable trade. This value also serves as a reminder to avoid sins resulting from inaccurate weighing or defective goods, and as a means of fostering sincerity between seller and buyer. These values ​​are in line with Islamic teachings, which have deeply influenced the cultural patterns and local wisdom of the Banjar people, particularly in the traditional river-based trading system.